2011
DOI: 10.1002/arp.400
|View full text |Cite
|
Sign up to set email alerts
|

Situating Remote Sensing in Anthropological Archaeology

Abstract: Productive applications of geophysics to anthropological questions in American archaeology necessarily involve specific research questions or agendas.While only some anthropological questions can be addressed by shallow geophysics, these techniquesprovide an opportunity to address someimportant questionsthat are fundamental to archaeology. One such agenda is the investigation of 'persistent places' , which is rooted in anthropological inquiry and which can be investigated, at least in part, by shallow geophysi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
46
0

Year Published

2014
2014
2023
2023

Publication Types

Select...
5
2

Relationship

1
6

Authors

Journals

citations
Cited by 53 publications
(46 citation statements)
references
References 34 publications
0
46
0
Order By: Relevance
“…At both sites, the value of geophysics for prospection went well beyond simply locating subsurface features to excavate, though this step nevertheless played a crucial role. For one thing, the initial geophysical surveys at both Washausen and Garden Creek were designed to address, and then successfully answered, specific archaeological questions related to site extent and spatial organisation (as Thompson et al, [2011] have previously demonstrated). Both case studies show the value of undertaking extensive geophysical survey at the outset of an archaeological project for understanding the function and archaeological potential of a site.…”
Section: Discussionmentioning
confidence: 99%
See 3 more Smart Citations
“…At both sites, the value of geophysics for prospection went well beyond simply locating subsurface features to excavate, though this step nevertheless played a crucial role. For one thing, the initial geophysical surveys at both Washausen and Garden Creek were designed to address, and then successfully answered, specific archaeological questions related to site extent and spatial organisation (as Thompson et al, [2011] have previously demonstrated). Both case studies show the value of undertaking extensive geophysical survey at the outset of an archaeological project for understanding the function and archaeological potential of a site.…”
Section: Discussionmentioning
confidence: 99%
“…Citing examples from the U.K., he determined this resulted from poor communication between geophysicists and archaeologists. Nearly two decades on, this issue is still commonplace in many regions; however, recent calls for the use of non-invasive methods "beyond mere prospection" (Conyers and Leckebusch, 2010) and for "inquiry-based geophysics" (Thompson et al, 2011) show that collaborative interactions between the two methodologies can accomplish more than either strategy used in isolation. For example, while traditional methods like surface collections, shovel testing, and excavation can identify cultural material and provide diagnostic dating evidence from a subset of subsurface features, extensive geophysical survey can assist in identifying the presence (or absence), type, organisation, and extent of buried features across a site, taskscape, or landscape.…”
Section: Introductionmentioning
confidence: 99%
See 2 more Smart Citations
“…As McKinnon and Haley explain (p. 2), this involves integration with anthropological theory and interpretations that go beyond simply mapping sites and locating features. They follow Aspinall, Gaffney, and Schmidt (), Kvamme (), and Thompson, Arnold, Pluckhahn, and VanDerwarker () in encouraging use as primary data for investigating, interpreting, evaluating and explaining the past. Case studies are organized into four major themes: (1) Site Structure and Community Organization; (2) Technological Transformation and Economic Change; (3) Archaeological Landscapes; and (4) Earthen Mound Construction and Composition.…”
mentioning
confidence: 98%